Preconception exposure to dibutyl phthalate (DBP) impairs spermatogenesis by activating NF-κB/COX-2/RANKL signaling in Sertoli cells. (30th May 2022) - Xie, Zhiwen; Liu, Shiwei; Hua, Shan; Wu, Lei; Zhang, Yongqing; Zhu, Yiping; Shi, Fei; Jiang, Juntao
Abstract: Dibutyl phthalate (DBP) is an endocrine disruptor, which causes male reproductive dysfunction in rodents. Previous researches demonstrated that DBP exposure impaired spermatogenesis, however, the molecular mechanism is largely uncovered. In this study, we demonstrated that prenatal exposure to DBP increased receptor activator of nuclear factor-κB ligand (RANKL) expression in seminiferous tubules, especially in Sertoli cells. Western blot and immunofluorescence assays showed that DBP induced up-regulation of RANKL expression in Sertoli cells. Furthermore, experimental data showed that DBP increased COX-2 and p-p65 expression in Sertoli cells and depleting COX-2 and p-p65 by specific inhibitor NS3–98 and BAY117082 could partially abolish DBP induced up-regulation of RANKL. Moreover, the content of RANKL in Sertoli cells was significantly increased after DBP exposure by conducting enzyme linked immunosorbent assay (ELISA), which promoted spermatogonial stem cells (C18–4 cells) apoptosis in a paracrine manner. Together, our data demonstrated that a novel mechanism for DBP induced impairment of spermatogenesis by activating NF-κB/COX-2/RANKL signaling in Sertoli cells, and provided a diagnostic and therapeutic target. Highlights: Sertoli cells were a target of DBP in testis. The NF-κB/COX-2 signaling pathway was activated by DBP in Sertoli cells. DBP induced the expression of RANKL in vivo and in vitro. There was a crosstalk between Sertoli cells and spermatogonial stem cells. RANKL secreted by Sertoli cells resulted in the apoptosis of spermatogonial stem cells.